КРИМІНАЛЬНИЙ АКЦІОНІЗМ: ВІД СИМВОЛІЧНОСТІ СУБ’ЄКТА ДО СУБ’ЄКТИВІЗАЦІЇ СИМВОЛУ (Вісник Кримінологічної асоціації України, 2022)
The article is devoted to the study of the nature of criminal actionism. It is established that actionism is an invasion of a symbol into being, aggression of a simulacrum, transformation of being into a symbol with partial preservation of ontology; such a simulative deontologization and ontological simulativity. It is dialogical in nature, as any manifesto presupposes the existence of another subject. At the same time, not every manifestation is actionism, but only that which is directly experienced as a process, it has existential significance. It is concluded that criminal actionism is an existential phenomenon of dialogic manifestation of personally and/or collectively significant symbolism of social life, manifested in performative criminal practices (hooliganism, vandalism, terrorism, extremism, unleashing and waging aggressive war). Such types of criminal actionism as external (ordinary and extraordinary) and internal, as well as minority and majority (positive and negative) are singled out and characterized.
Keywords: actionism, manifesto, dialogue, existence, performance, symbol, crime, criminal actionism.